Good governance, working definitions and components - Ghangas, Vinita (Innovative Research Thoughts, 2017)
Almost all major development institutions today say that promoting good governance is an important part of their agendas. Despite this consensus, ‘good governance’ is an extremely elusive objective: it means different things to different organizations and to different actors within these organizations. This study provides a review of donor approaches and discusses good governance as a concept. While methodological discussions are often esoteric, the study argues that this one has real world relevance to development policy because donor agencies regularly measure and assess the quality of governance, condition assistance on these measurements, seek to design evidence-based policies, and justify their focus on good governance partly on the basis of claims that better governance promotes economic development. The weakness of the good governance concept calls into question each of these projects. Future work would do well to disaggregate the concept of good governance and refocus attention and analysis on its various disaggregated components, as defined here (e.g., democracy, the rule of law, efficient public management).